2020
DOI: 10.1007/s00382-020-05402-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvements of the coupled WRF-Lake model over Lake Nam Co, Central Tibetan Plateau

Abstract: A series of model sensitivity simulations are carried out to calibrate and improve the Weather Research and Forecasting Model coupled with a one-dimensional lake model (WRF-Lake) based on observations over Lake Nam Co. Using the default lake model parameters, the solution of WRF-Lake exhibits significant biases in both the lake thermodynamics and regional climatology, i.e., higher lake surface temperature (LST), earlier onset of summer thermal stratification, and overestimated near-surface air temperature and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 94 publications
0
32
0
Order By: Relevance
“…The 1‐D model considered the snow, lake water/ice, and soil sediment processes within a lake column (e.g., Gu et al., 2015). WRF‐Lake has undergone significant calibrations and has been applied in simulating the thermodynamics in LNC in offline or coupled settings (A. N. Huang et al., 2019; Wu et al., 2020). In this study, WRF‐Lake is run in un‐coupled mode for the same 8‐month duration using the same initial condition and surface forcing as POM.…”
Section: Methodsmentioning
confidence: 99%
“…The 1‐D model considered the snow, lake water/ice, and soil sediment processes within a lake column (e.g., Gu et al., 2015). WRF‐Lake has undergone significant calibrations and has been applied in simulating the thermodynamics in LNC in offline or coupled settings (A. N. Huang et al., 2019; Wu et al., 2020). In this study, WRF‐Lake is run in un‐coupled mode for the same 8‐month duration using the same initial condition and surface forcing as POM.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, CPRCMs are mainly atmospheric-only models. Large benefits could be achieved by adding Earth system components (Giorgi & Gao, 2018) to CPRCMs such as lake models (Wu et al, 2020), aerosol schemes (Chen, 2021), oceanic models providing improved sea surface temperature gradients (Van Pham et al, 2016), and more sophisticated surface schemes including irrigation (Qian et al, 2020) and groundwater interactions (Barlage et al, 2021).…”
Section: Evaluation Of Renewable Energy Resources and Wind Farm Impacts On Atmospheric Conditionsmentioning
confidence: 99%
“…Indeed, conducting monthly CPRCM simulations including or not the Lake Nam Co over the Tibetan Plateau, Dai et al (2018) found that the presence of the lake can increase precipitation up to 60% over and downwind the lake. However, CPRCM simulated lake effects are closely linked to the ability of the lake model to represent lake temperatures, dynamics, and initial conditions (Wu et al, 2020; Xu et al, 2017).…”
Section: Evidence Of Added Value In Cprcm Hindcast Simulationsmentioning
confidence: 99%
“…where Sn(z) and Sn(0) are the shortwave radiations at water depth z and at the water surface, respectively, and λe is the light extinction coefficient calculated as suggested by Wu et al (2020):…”
Section: Shortwave Radiationmentioning
confidence: 99%